Kualitas Susu Di Tingkat Peternak, Pengumpul Dan Pengecer Di Yogyakarta Dan Sekitarnya - Wahyuni, Endang (2008)
Milk is most often produced on an industrial scale for human consumption. It is the most commonly consumed form of milk. Eighty-seven samples of milk were examined for their alcohol test, acidity, pH value, methylen blue reductase test (MBRT), number of bacteria. Eschericia coli and Staphylococcus aureus, and measured the fat quantity. Negative alcohol test were found 66.67% of 40 dairy farming milk, 45.45% of 34 milkcan collection, and 89.47% of 19 milk retail. Milk samples which have a titrable acidity concentration of 0.13 to 0.18% at level between 6.6 to 6.7 are 42.5% of dairy farming milk, 26,47% of milkcan collection, and 5,26% of milk retail. In methylen blue reductase test for microbial activity, milk that is decolorized <2 hours are 12,5% of dairy farming milk, 64.71% of milkcan collection, and 10,53% of milk retail. Total bacterial count <1.00x106cfu/ml are 52,5% of dairy farming milk and 55.88% of milkcan collection, meanwhile total bacteria count<3.00x104cfu/ml are 36.84% of milk retail. E.coli strains were isolated from 25 samples and Staphylococcus aureus starins from 26 samples and 22 samples were bacteriologically negative. The milk samples which have fat content>3% are 86.84% of dairy farming milk and 40% of milkcan collection, meanwhile <1.5% are 15.79% of retail milk. Microbiologically, milk quality from milk collector is lower than from milk farmer, meanwhile total bacteria of milk retail decreasedafter pasteurization process. The milk from collector had higher fat than farmer, meanwhile milk fat contents of milk retail have range with an average of fat content standard of pasteurized milk.